2021
DOI: 10.3389/fnagi.2021.625551
|View full text |Cite
|
Sign up to set email alerts
|

Grip Strength and the Risk of Cognitive Decline and Dementia: A Systematic Review and Meta-Analysis of Longitudinal Cohort Studies

Abstract: Purpose: Loss of grip strength and cognitive impairment are prevalent in the elderly, and they may share the pathogenesis in common. Several original studies have investigated the association between them, but the results remained controversial. In this systematic review and meta-analysis, we aimed to quantitatively determine the relationship between baseline grip strength and the risk of cognitive impairment and provide evidence for clinical work.Methods: We performed a systematic review using PubMed, EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 44 publications
9
67
1
1
Order By: Relevance
“…These declines, however, are small if compared to previous reports (Auyeung et al, 2014;Patel et al, 2018). Moreover, age-related changes in grip force may be especially multidetermined given its above-mentioned association with cognitive decline (Cui et al, 2021), and its relation to several neural substrates (Carson, 2018). Together, this may serve as an explanation why changes in grip force and FA are not significantly related to each other in our analyses.…”
Section: Cross-sectional and Longitudinal Brain-behavior Associationscontrasting
confidence: 59%
See 1 more Smart Citation
“…These declines, however, are small if compared to previous reports (Auyeung et al, 2014;Patel et al, 2018). Moreover, age-related changes in grip force may be especially multidetermined given its above-mentioned association with cognitive decline (Cui et al, 2021), and its relation to several neural substrates (Carson, 2018). Together, this may serve as an explanation why changes in grip force and FA are not significantly related to each other in our analyses.…”
Section: Cross-sectional and Longitudinal Brain-behavior Associationscontrasting
confidence: 59%
“…Of note, due to the lack of variance in the change trajectories of the motor speed tasks, we could only evaluate longitudinal levelchange and change-change associations of WM FA with motor strength in the grip force task. Very recently, grip force has been associated with cognitive decline in healthy aging and demented patients (Cui et al, 2021) and is therefore being discussed also as an early marker of cognitive degradation. While we are still in the beginning of understanding how changes in brain structure impact on changes in motor function, previous longitudinal studies on brain structure and cognitive performance have reported inconsistent results with respect to change-change associations, especially when examining healthy older adults (Salthouse, 2011;Oschwald et al, 2019a).…”
Section: Cross-sectional and Longitudinal Brain-behavior Associationsmentioning
confidence: 99%
“…Inter-instrument reliability was tested using intra-class correlation (ICC) assuming average fixed raters, i.e. ICC (3,1). The overall ICC value was computed across all data collectively, and an overall ICC of 0.909 ([0.87 -0.94]; 95% CI) indicates a good-to-excellent inter-instrument agreement between the two devices.…”
Section: Inter-instrument Reliability Between Gripable and Jamar+mentioning
confidence: 99%
“…Maximum grip strength (MGS) is a ubiquitous objective outcome measure for delineating hand functions, including the severity of upper limb impairment, improvement after hand surgery and functional progress after rehabilitation (or lack thereof). A weak grip is associated with poor health-related quality of life (HRQoL) (Sayer et al 2006), and individuals with impaired grip strength pose an increased risk of having a heart attack, stroke, and cognitive loss (Leong et al 2015, Cui et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum grip strength (MGS) is a ubiquitous objective outcome measure for delineating hand functions, including the severity of upper limb impairment, improvement after hand surgery and functional progress after rehabilitation (or lack thereof). A weak grip is associated with poor health-related quality of life (HRQoL) [ 1 ], and individuals with impaired grip strength pose an increased risk of having a heart attack, stroke, and cognitive loss [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%